2020
DOI: 10.1111/ejh.13367
|View full text |Cite
|
Sign up to set email alerts
|

All‐trans retinoic acid (ATRA)‐induced TFEB expression is required for myeloid differentiation in acute promyelocytic leukemia (APL)

Abstract: Objective In acute promyelocytic leukemia (APL), normal retinoid signaling is disrupted by an abnormal PML‐RARα fusion oncoprotein, leading to a block in cell differentiation. Therapeutic concentrations of all‐trans‐retinoic acid (ATRA) can restore retinoid‐induced transcription and promote degradation of the PML‐RARα protein. Autophagy is a catabolic pathway that utilizes lysosomal machinery to degrade intracellular material and facilitate cellular re‐modeling. Recent studies have identified autophagy as an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…Interestingly, the majority of the TFEB downstream targets from the different categories (lysosomal hydrolases and accessory proteins, lysosomal membrane, lysosomal acidification, non-lysosomal proteins involved in lysosomal biogenesis and autophagy) are negatively associated with FASN transcript levels in primary AML patient blasts from TCGA analyzed using the UCSC Xena platform (Goldman et al, 2019) and the Blood spot gene expression profiles data base (Bagger et al, 2016) ( Figure 5A, Supplementary Figures 4B-C Supplementary Table 1-2). Furthermore, analyzing RNA-seq data of NB4 cells treated with ATRA confirmed a reduction of FASN expression paralleled by increased TFEB and TFEB target gene transcript levels (Orfali et al, 2019) ( Figure 5B). To test if the FASN-mTOR pathway is involved in regulating TFEB activity, we analyzed the cellular localization of TFEB upon ATRA treatment in NB4 control and FASN depleted cells.…”
Section: Fasn Expression Negatively Affects Transcription Factor Eb (mentioning
confidence: 79%
See 3 more Smart Citations
“…Interestingly, the majority of the TFEB downstream targets from the different categories (lysosomal hydrolases and accessory proteins, lysosomal membrane, lysosomal acidification, non-lysosomal proteins involved in lysosomal biogenesis and autophagy) are negatively associated with FASN transcript levels in primary AML patient blasts from TCGA analyzed using the UCSC Xena platform (Goldman et al, 2019) and the Blood spot gene expression profiles data base (Bagger et al, 2016) ( Figure 5A, Supplementary Figures 4B-C Supplementary Table 1-2). Furthermore, analyzing RNA-seq data of NB4 cells treated with ATRA confirmed a reduction of FASN expression paralleled by increased TFEB and TFEB target gene transcript levels (Orfali et al, 2019) ( Figure 5B). To test if the FASN-mTOR pathway is involved in regulating TFEB activity, we analyzed the cellular localization of TFEB upon ATRA treatment in NB4 control and FASN depleted cells.…”
Section: Fasn Expression Negatively Affects Transcription Factor Eb (mentioning
confidence: 79%
“…We and others have demonstrated that autophagy gene expression is repressed in AML samples compared to granulocytes from healthy donors and that autophagy activity is essential for successful ATRA-induced APL differentiation (Isakson et al, 2010;Wang et al, 2011;Jin et al, 2018;Humbert et al, 2017;Brigger et al, 2014b;Watson et al, 2015;Orfali et al, 2015Orfali et al, , 2019. The decrease in FASN expression upon ATRA-induced differentiation cannot be explained solely by transcriptional regulation due to the long half-life of this protein (1-3 days) (Volpe & Vagelos, 1976;Weiss et al, 1986).…”
Section: Fasn Protein Is Degraded Via Macroautophagy During Atra-indumentioning
confidence: 91%
See 2 more Smart Citations
“…Our RNA sequencing data showed a 17.54‐fold increase in ISG15 gene expression in NB4 cells with ATRA treatment (Orfali et al , ) (Table ). We validated this finding by qPCR measurement of ISG15 expression in ATRA‐treated NB4 cells at 72 h, which showed a 23‐fold increase in expression in differentiating cells (**** P ≤ 0.0001).…”
Section: Resultsmentioning
confidence: 99%